Niveles de autoestima en estudiantes del programa de enfermería en la Universidad Antonio Nariño, Sede Bogotá (2021)
Self-esteem is one of the most important aspects in the life of any person, which is why, especially psychology, has carried out research on this subject. And although self-esteem is a term that is used in everyday life, its importance for the lives of people in society is seldom rationalized. Objective: To identify the levels of self-esteem of the students of the Nursing program of the Antonio Nariño University.